Relevansi Doktrin Promissory Estoppel dalam Pembentukan Hukum Kontrak Bisnis Indonesia - Margareta Gita Sirait; Ery Agus Priyono (Journal of Creative Student Research, 2026)
This study examines the relevance of the doctrine of promissory estoppel in the formation of business contract law in Indonesia. The development of modern business transactions demonstrates that legal relationships are no longer solely based on formal written contracts, but also arise during pre-contractual stages such as offering letters, memorandums of understanding, purchase orders, and electronic communications. This condition often creates legal uncertainty when one party withdraws a promise after the other party has relied on it and suffered losses. This research employs a normative legal method using conceptual and statutory approaches supported by literature studies. The findings indicate that the doctrine of promissory estoppel is relevant to strengthening legal protection, good faith, proportionality, and legal certainty within Indonesian business contracts. Although originating from the common law system, the doctrine substantively aligns with principles recognized in Indonesian contract law. The study concludes that harmonizing promissory estoppel with the national civil law system may contribute to a more adaptive and equitable business contract framework in Indonesia.